Comparison of combination of mifepristone and misoprostol with misoprostol alone in management of intrauterine death - Rajkumar,; Sharma, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Intrauterine fetal death is one of the most devastating obstetric complications. A clinically accepted definition of IUFD is the death of fetus at or after 20 weeks of pregnancy, but for international comparison WHO has now recommended IUFD as a baby born with no signs of life at or after 28 weeks of gestation. Methods: The prospective analytical study was be conducted in the department of obstetrics and gynecology at government medical college and J. K. Loan Hospital Kota over a 1 June 2021 to 30 November 2022 year women with intrauterine death after 28 weeks of gestation are studied. 120 pregnant women were divided randomly, alternatively into two groups of 60 each. Group I (combination regimen)- women received 200 mg mifepristone orally and misoprostol after 24 hours. Group II (misoprostol group). Results: We included 120 patients with late IUD and found that the mean induction to delivery interval was 9.98 hours in combination group where as it was 14.2 hours in misoprostol only group. This provides a good alternate regimen in the management of late intrauterine deaths. Conclusions: The combination of mifepristone and misoprostol for induction of labour in IUFD has shorter induction to delivery interval and lesser number of misoprostol doses usage when compared to only-misoprostol group. However, conventional regimen with misoprostol alone may be appropriate in settings where cost is a prohibitive factor.